POTASSIUM FERTILIZATION MANAGEMENT IN COMMON BEAN PROTECTION AGAINST COLLETOTRICHUM LINDEMUTHIANUM - Wallysson Nascimento Lima; Deurimar Herênio Gonçalves Júnior; Anatércia Ferreira Alves (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
Anthracnose of common bean caused by the fungus Colletotrichum lindemuthianum is considered one of the most important fungal diseases that attacks the aerial part of the common bean for causing significant losses in final productivity. Potassium is one of the elements that is involved in the defense of the plant. Thus, the objective was to evaluate the effect of potassium doses in the control of anthracnose in three common bean cultivars. The design used was completely randomized with five treatments in three repetitions. The severity of the disease was obtained at 15 days after inoculation using a diagrammatic scale of notes and by counting the number of lesions in the central and lateral leaflets and the length of the lesions in the midrib of the central leaflet.